2021
DOI: 10.1016/j.chemosphere.2020.128004
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis and characterization of anatase TiO2/g-CN composites for enhanced photoactivity under UV–visible spectrum

Abstract: For the purpose of atmospheric NO removal, anatase TiO2/g-CN photocatalytic composites were prepared by using a facile template-free calcination route in atmospheric conditions. Considerably fiscal NP400 and laboratory-grade melamine were used as the precursor of the composites. Additionally, samples were prepared with different wt. ratios of TiO2 and melamine by using two distinct calcination temperatures (550°C/600°C). The morphological attributes of the composites were assessed with X-ray diffraction, scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The diffraction peaks at 25.20, 35.92, and 63.13° are attributed to (101), (105), and (204) crystalline planes of TiO 2 (anatase). 12 However, it was very difficult to isolate all crystalline planes of the anatase. The shielding effect of Fe 3 O 4 had taken place during the precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peaks at 25.20, 35.92, and 63.13° are attributed to (101), (105), and (204) crystalline planes of TiO 2 (anatase). 12 However, it was very difficult to isolate all crystalline planes of the anatase. The shielding effect of Fe 3 O 4 had taken place during the precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear from these equations that the adsorbed O 2 and H 2 O play a very significant role in the photooxidation of atmospheric NO. During photooxidation, O 2 is employed to trap the generated e − on the TiO 2 surface, and •OH radicals are formed from H 2 O by confining the generated h + on the TiO 2 surface, leading to NO oxidation and produce by-products like NO 2 and NO 3 − [14,15]. Therefore, when the sample is subjected to UV radiation, the photooxidation of NO takes place spontaneously.…”
Section: Mechanism Of No Removalmentioning
confidence: 99%
“…A laboratory-scale photocatalytic reactor was used, following ISO 22197-1, to examine the extent of NO x photooxidation. The specifics of the method are listed elsewhere [14][15][16]. Figure 10 shows the diagram of the device used to test the photocatalytic efficiency of the as-prepared samples.…”
Section: Removal Of No X Under Uv Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…g-C 3 N 4 is a good semiconductor material with application potential that is metal free and has visible light responsiveness [ 8 , 9 , 10 ]. However, researchers found that g-C 3 N 4 still has many disadvantages such as low utilization of visible light, poor photoelectric conversion efficiency, and low specific surface area [ 11 ]. Since Serpone et al [ 12 ] first reported that a solid–solid heterojunction interface with good contact can be constructed from different coupled semiconductor materials to promote electron transfer between particles, more and more researchers have paid attention to different semiconductor materials.…”
Section: Introductionmentioning
confidence: 99%